2022
DOI: 10.1007/s40710-022-00615-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Photocatalytic Degradation of Nevirapine in Wastewater Using the UV/TiO2/H2O2 Process

Abstract: This work sought to study the elimination of NVP from simulated wastewater using the UV/TiO 2 /H 2 O 2 system. The main objectives were to evaluate the in uence of operating parameters, reaction kinetics, contributing reactive species, degradation pathway, and catalyst reusability. The research surface methodology (RSM) was utilized for optimizing process variables and for statistical analysis. Five process variables (pH, NVP concentration, TiO 2 dosage, H 2 O 2 concentration, and irradiation time) were optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The mixed phase TiO2 (anatase (A) 77%: rutile (R)23%) synthesized in our previous work was employed in this study (Ncube et al 2023). The authors demonstrated a band gap of 3.16 eV, which approximated 3.15 eV reported for the commercial mixed-phase TiO2-P25 (Coutts et al 2016), while being lower than the widely reported 3.2 eV for single-phase TiO2.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…The mixed phase TiO2 (anatase (A) 77%: rutile (R)23%) synthesized in our previous work was employed in this study (Ncube et al 2023). The authors demonstrated a band gap of 3.16 eV, which approximated 3.15 eV reported for the commercial mixed-phase TiO2-P25 (Coutts et al 2016), while being lower than the widely reported 3.2 eV for single-phase TiO2.…”
Section: Introductionmentioning
confidence: 72%
“…To prepare working standards, appropriate quantities of FTC, LVD and TFV stock solutions were spiked into ultra-pure water (UPW) in a 600 ml beaker to achieve environmentally relevant concentrations (FTC, LVD) and to match the LC/MS sensitivity (TFV) (Nannou et al 2020;Alvarez-Corena et al 2016). Mixed-phase TiO2 (77% A/23% R) synthesized in our previous work was employed as the photocatalyst (Ncube et al 2023).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations